LncRNA miR205HG hinders HNRNPA0 translation: anti‐oncogenic effects in esophageal carcinoma - Xiaoying Dong; Xuyuan Chen; Di Lu; Dingwei Diao; Xiguang Liu; Shijie Mai; Siyang Feng; Gang Xiong (Molecular Oncology, 2022)
Esophageal carcinoma (ESCA) affects 4 450 000 people and causes approximately 400 000 deaths annually worldwide, making it the sixth most lethal and eighth most common cancer. Patients with ESCA are often diagnosed at the later stages in which cancer cell metastasis is the main factor contributing to the low 5‐year survival rate (< 20%) of this disease. Long noncoding RNAs (lncRNAs) are a group of regulatory RNAs with a length of > 200 nucleotides but which fail to encode proteins. In this study, by using real‐time quantitative PCR, we found that the expression of the miR205 host gene (miR205HG; a lncRNA) was downregulated in ESCA tumors when compared with normal esophageal tissues or adjacent normal tissues of tumors. Furthermore, we demonstrated that miR205HG modulates the expression of extracellular matrix‐related genes in ESCA cells. In the transwell assay, downregulation of miR205HG contributes to migration and invasion of ESCA cells. In relation to the mechanism, our data show that miR205HG interacts with heterogeneous nuclear ribonucleoprotein A0 (HNRNPA0) mRNA and then hamper its translation by interacting with lin‐28 homolog A (LIN28A). Altogether, we highlight that the miR205HG‐HNRNPA0 axis is implicated in the migration and invasion of ESCA cells and that these members of this pathway may serve as therapeutic targets to inhibit metastasis of ESCA.